# maths-trignometry

posted by .

Prove that
tan-1 (1/7) + tan-1 (1/13) = tan-1(2/9)

• maths-trignometry -

let tanA = 1/7 and tanB = 1/13

then tan(A+B) = (tanA + tanB)/( 1 - tanAtanB)
= (1/7 + 1/13)/(1 - (1/7)(1/13) )
= (20/91) / (90/91) = 20/90 = 2/9

and if we let tanC = 2/9
then A + B = C

thus tan^-1 (1/7) + tan^-1 (1/13) = tan^-1 (2/9)

take 2nd Tan (1/7) = 8.13010..
take 2nd Tan(1/13) = 4.39871
take 2nd Tan(2/9) = 12.5288..

## Similar Questions

1. ### Trig - tan 15° using composite argument?

tan 15° tan (45°-30°) (tan 45° - tan 30°)/1+ tan 45°tan30° (1-√3/3)/(1+1√3/3) then i donnt what to do/ chancel out. Can someone finish it if i didn't get it wrong. thanks in advance
2. ### Trigonometry

Find the exact value of tan(a-b) sin a = 4/5, -3pi/2<a<-pi; tan b = -sqrt2, pi/2<b<pi identity used is: tan(a-b)=(tan a-tan b)/1+tan a tan b simplify answer using radicals. (a is alpha, b is beta)
3. ### trignometry

1. if sin 2A = Psin2B, prove that tan(A+B)/tan(A-B)=P+1/P-1.
4. ### Trigonometry

1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two decimal places. 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y 10.Prove that 1+tanθ/1-tanθ = sec^2θ+2tanθ/1-tan^2θ 17.Prove that …
5. ### precalculus

For each of the following determine whether or not it is an identity and prove your result. a. cos(x)sec(x)-sin^2(x)=cos^2(x) b. tan(x+(pi/4))= (tan(x)+1)/(1-tan(x)) c. (cos(x+y))/(cos(x-y))= (1-tan(x)tan(y))/(1+tan(x)tan(y)) d. (tan(x)+sin(x))/(1+cos(x))=tan(x) …
6. ### Trigonometry desperate help, clueless girl here

2. solve cos 2x-3sin x cos 2x=0 for the principal values to two decimal places. 3. solve tan^2 + tan x-1= 0 for the principal values to two decimal places. 4. Prove that tan^2(x) -1 + cos^2(x) = tan^2(x) sin^2 (x). 5.Prove that tan(x) …
7. ### Math-Trigonometry

Show that if A, B, and C are the angles of an acute triangle, then tan A + tan B + tan C = tan A tan B tan C. I tried drawing perpendiculars and stuff but it doesn't seem to work?
8. ### trignometry

Tan4x=4tanx(1-tan^x)/1-6tan^x+tan^^x ,prove
9. ### math 105

Prove that tan(A+B+C) =(tan A + tan B tan C - tanAtanBtanC) ÷(1-tanAtanB-tanBtanC-tanAtanC)
10. ### basic maths trignometry

prove that secx - tanx = 1 -tan x/2 /1 + tan x/2

More Similar Questions

Post a New Question